Dispersion of heavy gases – Experimental results and numerical simulations. Issue 3 (20th November 2014) - Rauchegger, Christian; Bayley, Susan; Schröder, Volkmar; Thévenin, Dominique
<x xml:space="preserve">Abstract</x> The hazardous potential of accidental heavy gas releases, especially those involving flammable and toxic gases, is widely known. In order to predict the area in which these gases are in hazardous concentrations, an estimation of the dispersion of these gases must be carried out. While the hazardous area for flammable heavy gases is determined by the lower flammability limit (ca. >1 vol%), the release of toxic heavy gases can result in a much larger hazardous area. Toxic gases, even in very low concentrations (ca. <3, 000 ppm), have the potential to be highly damaging. State‐of‐the‐art dispersion models, such as the VDI Guideline 3783, can be used to estimate the dispersion of heavy gases. However, VDI 3783 gives no method for the prediction of the height and width of a heavy gas cloud, which are both required for quantitative risk analysis as well as for a possible coupling of a Lagrangian particle model with the VDI 3783 heavy gas dispersion model. Therefore, further calculation methods were used to describe these dimensions and were evaluated against experimental studies of the length, width, and height of the heavy and neutral gas field. In addition to that the influence of the source height on the heavy gas dispersion was also examined. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 280–285, 2015